Copper Mineralization of the Mesozoic Passaic Formation, Northern New Jersey - J. H. Puffer (The Minerals, Metals and Materials Society, 1987)
The copper mineralization of the Mesozoic Passaic Formation of New Jersey is typical of copper deposits in eastern North American Mesozoic sediments. Most such deposits are located at the base of the first of several basalt flows that are interbedded with continental, red-bed sediments. The copper mineralization is similar in most respects to that of the Keweenawan Basalts of the Lake Superior area. The first basaltic flow units of the eastern North American Mesozoic basins, and the Keweenawan Basalts, are continental quartz tholeiites of similar chemical composition and copper contents. The copper minerals and associated zeolite facies metamorphic mineral assemblages of these two rock units are also approximately the same. Stoiber and Davidson (1959) suggested that Keweenawan copper was mobilized and concentrated during metamorphism. The evidence pertaining to the Mesozoic copper deposits of New Jersey is consistent with such an interpretation and also with DeVore's (1955) suggestion that ore fluids commonly arise as a result of the mobility of metals under metamorphic conditions. There is additional evidence that final metamorphic concentration of Mesozoic copper was preceded by an initial stage of hydrothermal precipitation related to fluids emitted by basaltic magma.